A fórmula do capital escravista-mercantil - Costa, Iraci del Nero da; Pires, Júlio Manuel (Estudos Econômicos (São Paulo), 1994)
This paper supplements the article intitled "Consideragoes sobre o capital escravista-mercantir (Cf. Estudos Econdmicos, v. 24, n. 1, p. 129-143, jan./abr. 1994), in which the existence of a specific form of capital is proposed and explained. The purpose now is to present its formula, define its constituent elements, describe its development in stages and show how the stages are linked to each other.